Facebook e educação : tecendo caminhos a partir de uma prática pedagógica com os alunos do ensino médio - Gengnagel, Claudionei Lucimar (2013)
This study aims to determine the potential and limitations of Facebook in the process of motivating students of 2nd year high school Colégio Salvatoriano Bom Conselho de Passo Fundo/RS. Therefore, the search for theoretical and practical activity developed sought to provide answers to the following problem: What are the consequences of the use of Facebook in the process of students' motivation for teaching the discipline of history? In the scope of this study we chose to discuss some concepts stemming from the culture learning, interaction and importance of motivation for the teaching process. Welcome to encounter these issues, we analyzed the processes that underlie the virtualization of learning as well as the concepts of cyberspace and finally, the possibilities arising from the integration of social networks, especially Facebook, in the educational context. What we found on the net is that intrinsic motivation is very difficult to occur naturally in students, since many are still rooted in the context of conventional and quantitative education, where only worthwhile to learn or participate in an activity if we get something extra in return, preferably numeric - note. Experienced in the context of the Facebook group, the possible interaction was very different from what actually materialized. While there are numerous possibilities, which noted it was a moderate interaction with some very active students, but also many other totally null in the process. But even with limited interaction and change of motivation in students to enter the world of the same teacher, it was found that the rigid hierarchy of the classroom is broken, approaching the class content and the discipline of history.